Anpassung an den Klimawandel. Priorisierung von Maßnahmen innerhalb der Deutschen Anpassungsstrategie. - Vetter, Andreas; Schauser, Inke (Oekom, 2013)
Was muss zuerst unternommen werden, um den Folgen des Klimawandels zu begegnen? Mit einem kriterienbasierten Priorisierungskonzept kann diese Frage im Rahmen der Deutschen Anpassungsstrategie an den Klimawandel beantwortet werden. Maßnahmen zur Anpassung an den Klimawandel lassen sich damit sektorenübergreifend auswählen und bewerten.

Despite the success of some environmental and sustainability initiatives and measures in policy-making, business and society, overall trends follow an unsustainable path. Especially in the field of production a rid consumption of goods and services, environmental sustainability and social equality remain critical challenges. Therefore new approaches are needed alongside existing strategies and policy instruments. The sharing economy has the potential to provide a new pathway to sustainability and transdisciplinary sustainability science has the opportunity to co-shape and accompany this pathway.
Adaption to Climate Change. Prioritizing Measures in the German Adaption Strategy.
Keywords: Umweltschutz; Umweltpolitik; Klima; Effektivität; Bewertungskriterium; Klimawandel; Klimaschutz; Klimaanpassung; Aktionsplan